2017
DOI: 10.1021/acs.chemmater.7b01284
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Charge Carrier Transport and Surface States in CuFeO2 Photocathodes

Abstract: Interest in delafossite (CuFeO2) as a candidate p-type photocathode for photoelectrochemical (PEC) solar fuel production has recently been increasing, mainly due to its excellent stability in aqueous environments and favorable light absorption properties. However, its PEC performance has remained poor for reasons that have not yet been specifically determined. Herein, we report a detailed investigation on sol–gel-processed CuFeO2 with a range of spectroscopic, PEC, and microscopy techniques aimed at unraveling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
155
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 149 publications
(165 citation statements)
references
References 58 publications
(133 reference statements)
7
155
2
1
Order By: Relevance
“…Figure a shows the range of Fermi level positions that were obtained after calcining the 2H CuFeO 2 pellets and after establishing the interfaces of 2H CuFeO 2 with water and ITO. According to literature, the VBM of 3R CuFeO 2 is situated between 1.0 –1.4 eV versus RHE and the CBM should be within −0.1 to −0.5 eV versus RHE . For 2H CuFeO 2 a similar valence band position can be assumed due to the similarity of the VBM of Cu‐delafossites in general as well of that of different polytypes .…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…Figure a shows the range of Fermi level positions that were obtained after calcining the 2H CuFeO 2 pellets and after establishing the interfaces of 2H CuFeO 2 with water and ITO. According to literature, the VBM of 3R CuFeO 2 is situated between 1.0 –1.4 eV versus RHE and the CBM should be within −0.1 to −0.5 eV versus RHE . For 2H CuFeO 2 a similar valence band position can be assumed due to the similarity of the VBM of Cu‐delafossites in general as well of that of different polytypes .…”
Section: Resultsmentioning
confidence: 89%
“…The inability of any of the heterostructured 2H CuFeO 2 powders to produce high amounts of hydrogen through sacrificial water splitting is a remarkable phenomenon. Recently, Prévot et al showed through a set of photoelectrochemical measurements with varied redox systems that 3R CuFeO 2 thin films suffer from Fermi level pinning at a defect level positioned at about 0.7 eV versus normal hydrogen electrode (NHE) . According to the authors the Fermi level pinning was due to surface states caused by a metal hydroxide surface layer.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[4][5][6][7]46] To investigate the charge transport/transfer behaviors for both IO and planar CuFeO 2 -based photocathodes, electrochemical impedance spectroscopy (EIS) measurements were carried out in argon-purged 1 m NaOH electrolyte under simulated solar illumination as shown in Figure S10 (Supporting Information). [9][10][11][12][13] Surprisingly, unlike the planar CuFeO 2 , the IO CuFeO 2 /C 60 /CoFe LDH photocathode shows no loss of quantum efficiency as the incident photon energy decreases from 400 to 700 nm, which has not been observed for ternary oxide-based photocathodes. According to the diffusion-recombination model, the resistance R 1 obtained from the semicircular corresponds to the resistance for the charge transport and transfer.…”
Section: Resultsmentioning
confidence: 99%